Photocatalyst carrying a cocatalyst on its surface and method for producing said photocatalyst

A two-step method of impregnation and photoelectrodeposition supports co-catalysts on photocatalysts, addressing random adsorption issues and achieving enhanced hydrogen generation rates.

JP7599269B2Active Publication Date: 2024-12-13MITSUBISHI CHEM CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2019041808
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-03-07
Publication Date
2024-12-13
Estimated Expiration
2039-03-07

AI Technical Summary

Technical Problem

Existing methods for supporting co-catalysts on photocatalysts, such as impregnation and photoelectrodeposition, result in random adsorption and limited concentration of co-catalysts near reaction sites, leading to reduced hydrogen generation ability.

Method used

A two-step method involving impregnation followed by photoelectrodeposition is used to support co-catalysts, concentrating them near high-activity reaction sites, enhancing photocatalytic activity.

Benefits of technology

The method achieves a photocatalyst with significantly higher hydrogen generation ability, exceeding 250 μmol/h in methanol aqueous solution under visible light irradiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599269000006
    Figure 0007599269000006
  • Figure 0007599269000007
    Figure 0007599269000007
  • Figure 0007599269000008
    Figure 0007599269000008
Patent Text Reader

Abstract

To provide a photocatalyst on which a cocatalyst having a higher hydrogen generation ability is supported.SOLUTION: A method for producing a photocatalyst with a cocatalyst supported on the surface, has a first step of allowing a cocatalyst to be supported on the surface of a photocatalyst by impregnation, and a second step of allowing the same cocatalyst as the cocatalyst used in the first step to be supported on the surface of the photocatalyst having undergone the first step by photo-electro deposition.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photocatalyst having a co-catalyst supported on its surface, and a method for producing the same. [Background technology]

[0002] In order to improve the catalytic efficiency of photocatalysts, co-catalysts are supported on the surface of the photocatalyst. There are two main methods known for supporting co-catalysts on the surface of photocatalysts: the impregnation method (also called the adsorption method) and the photoelectrodeposition method.

[0003] The impregnation method is a method in which a co-catalyst or its precursor (hereinafter referred to as the co-catalyst, etc.) is adsorbed onto the surface of a photocatalyst and then reduced using hydrogen, alcohol, or ammonia, thereby supporting the co-catalyst, etc., on the surface of the photocatalyst. For example, Non-Patent Document 1 reports on the impregnation method, that a complete water decomposition reaction can be achieved by a photocatalyst that combines BaTaO2N (hereinafter referred to as Pt / BaTaO2N) supported with Pt as a co-catalyst prepared by the impregnation method and WO3 supported with Pt. The hydrogen production rate in a methanol aqueous solution using 0.3 wt% Pt / BaTaO2N was 50 μmol h -1 It has been reported that the

[0004] On the other hand, the photoelectrodeposition method is a method in which a photocatalyst is dispersed in a solution containing a cocatalyst, and the dispersion is irradiated with light to reduce the cocatalyst, thereby supporting the cocatalyst on the surface of the photocatalyst. The photocatalyst is excited by light irradiation, and the cocatalyst is adsorbed on the photocatalyst and reduced, so that the cocatalyst is efficiently attached to the reaction site portion, and the cocatalyst can be supported on the portion. For example, Non-Patent Document 2, which is related to the photoelectrodeposition method, reports that the Ru cocatalyst supported on TaON by the photoelectrodeposition method has overwhelmingly higher activity than other precious metals (Pt, Ir, etc.). Note that BaTaO2N has low activity when supporting a cocatalyst by the photoelectrodeposition method, so as far as the inventors know, there is no example of supporting a cocatalyst on BaTaO2N by the photoelectrodeposition method with an effect exceeding that of the impregnation method.

[0005] Furthermore, Patent Document 1 proposes supporting an oxidation reaction promoter and a reduction reaction promoter on a photocatalyst by using both an adsorption support method and a photoelectrodeposition support method in combination, and claims that this enables a water splitting reaction to be carried out with high activity. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-173102 A [Non-patent literature]

[0007] [Non-Patent Document 1] Higashi, M. et al. Chem. Mater. 2009, 21, 1543-1549 [Non-Patent Document 2] Solid State Iconics 172(2004),591-595 Summary of the Invention [Problem to be solved by the invention]

[0008] The inventors have studied and found that, in the above two methods of supporting a co-catalyst on the surface of a photocatalyst, the amount of catalyst supported on the photocatalyst and the hydrogen generation ability are not simply proportional. In other words, in the impregnation method, the position where the co-catalyst is adsorbed on the photocatalyst is random, and the adsorption site cannot be controlled at all, so even if the amount of the co-catalyst is increased, the hydrogen generation ability does not improve accordingly. In the photoelectrodeposition method, a compound that is a precursor of a co-catalyst is adsorbed near the reaction site of the photocatalyst and The co-catalyst is supported only after it is reduced by the excited electrons. Therefore, the support rate of the co-catalyst is greatly affected by the reaction characteristics of the photocatalyst, and even if the amount of the co-catalyst in the solution is increased, it is not possible to increase the amount of the co-catalyst supported by the photocatalyst, or the co-catalyst is supported only at a small number of reaction sites, causing the co-catalyst to grow into large particles, making it difficult to support the co-catalyst in a highly dispersed manner. The present invention is devised to solve the above-mentioned problems, and provides a photocatalyst carrying a promoter having higher hydrogen generation ability. [Means for solving the problem]

[0009] As a result of intensive research aimed at solving the above problems, the inventors discovered that the activity of a photocatalyst can be dramatically improved by first supporting a co-catalyst on the photocatalyst by an impregnation method, and then supporting a similar co-catalyst on the photocatalyst by a photoelectrodeposition method, thereby completing the present invention. Although the reason why the present invention can dramatically improve the activity of photocatalysts is unclear, the present inventors speculate as follows. That is, the cocatalyst portion supported near the reaction site among the cocatalysts supported by the impregnation method becomes highly active when the cocatalyst is supported by the photoelectrodeposition method carried out thereafter, because the activity of the supported cocatalyst is added to the activity that the photocatalyst originally has. Therefore, compared with the case where the cocatalyst is simply supported on the photocatalyst by the photoelectrodeposition method, the cocatalyst can be concentrated near the reaction site of the photocatalyst, and furthermore, the cocatalyst is supported in a more concentrated manner near the reaction site with the highest activity among the reaction sites, so the present inventors believe that the photocatalyst supported by the above method exhibits a very high activity compared to the amount of the cocatalyst supported. The present invention includes the following gist.

[0010] (1) A method for producing a photocatalyst having a co-catalyst supported on its surface, comprising the steps of: A first step of supporting a co-catalyst on the surface of the photocatalyst by impregnation; and A second step of supporting a co-catalyst similar to the co-catalyst used in the first step on the surface of the photocatalyst that has been subjected to the first step by a photoelectrodeposition method; A method for producing a photocatalyst comprising the steps of: (2) The method for producing a photocatalyst according to (1), wherein the amount of the co-catalyst supported on the photocatalyst in the first step is 1 wt % or less. (3) The method for producing a photocatalyst according to (1) or (2), wherein the co-catalyst comprises one or more members selected from the group consisting of precious metals. (4) The method for producing a photocatalyst according to any one of (1) to (3), wherein the co-catalyst contains Pt. (5) The method for producing a photocatalyst according to any one of (1) to (4), wherein the photocatalyst contains a compound represented by the following formula (1): Ba (1-a) TaO (2-b) N (1-c) (1) (In the formula, a, b, and c satisfy -0.2≦a≦0.1, -0.4≦b≦0.2, and -0.1≦c≦0.3, respectively.) (6) The method for producing a photocatalyst according to any one of (1) to (5), wherein the first step includes a hydrogen reduction step of reducing the co-catalyst with hydrogen. (7) A co-catalyst-supported photocatalyst, comprising a photocatalyst containing a compound represented by the following formula (1) and 1 wt% or less of a co-catalyst containing one or more selected from the group consisting of precious metals, A co-catalyst-supported photocatalyst, in which 0.1 g of the co-catalyst-supported photocatalyst is added to 150 mL of a 15% aqueous methanol solution at 288 K, and hydrogen is generated by irradiating the photocatalyst with a 300 W xenon lamp. The rate of hydrogen generation is 250 μmol / h or more. Ba (1-a) TaO (2-b) N (1-c) (1) (In the formula, a, b, and c satisfy -0.2≦a≦0.1, -0.4≦b≦0.2, and -0.1≦c≦0.3, respectively.) (8) The photocatalyst according to (7), wherein the co-catalyst contains Pt. (9) a first step of supporting a co-catalyst on the surface of the photocatalyst by impregnation; and A photocatalyst is obtained by a second step of supporting a co-catalyst similar to the co-catalyst used in the first step on the surface of the photocatalyst that has been subjected to the first step by a photoelectrodeposition method. Effect of the Invention

[0011] According to the present invention, it is possible to provide a photocatalyst supporting a promoter having higher hydrogen generation ability. [Brief description of the drawings]

[0012] [Figure 1] This is the XRD measurement result of the prepared BaTaO2N. [Diagram 2] 1 shows the results of measuring the absorption spectrum of the prepared BaTaO2N. [Diagram 3] FIG. 2 is a diagram showing a flow of a method for producing a photocatalyst. [Figure 4] This is a TEM observation result of the prepared Pt / BaTaO2N. [Diagram 5] This is the SEM observation result of the prepared Pt / BaTaO2N. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below. However, the description of the constituent elements described below is one example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents, and can be implemented in various modifications within the scope of the gist of the present invention.

[0014] One embodiment of the present invention is a method for producing a photocatalyst having a co-catalyst supported on its surface, comprising a first step of supporting the co-catalyst on the surface of the photocatalyst by an impregnation method, and a second step of supporting a co-catalyst similar to the co-catalyst used in the first step on the surface of the photocatalyst that has undergone the first step by a photoelectrodeposition method.

[0015] (Photocatalyst) The photocatalyst is not particularly limited as long as it is a photocatalyst that can decompose water to generate hydrogen, and for example, a visible light responsive optical semiconductor can be used. Specifically, Bi2WO6, BiYWO6, InTaO4, InTaO4:Ni ("Optical semiconductor: M" indicates that the optical semiconductor is doped with M. The same applies below), TiO2:Ni, TiO2:Ru, TiO2:Rh, TiO2:Ni / Ta ("Optical semiconductor: M1 / M2" indicates that the optical semiconductor is co-doped with M1 and M2. The same applies below), TiO2:Ni / Nb, TiO2:Cr / Sb, TiO2:Ni / Sb, TiO2:Sb / Cu, TiO2:Rh / Sb, TiO2:Rh / Ta, TiO2: Rh / Nb, SrTiO3:Ni / Ta, SrTiO3:Ni / Nb, SrTiO3:Cr, SrTiO3:Cr / Sb, SrTiO3:Cr / Ta, SrTiO3:Cr / Nb, SrTiO3:Cr / W, SrTiO3:Mn, SrTiO3:Ru, SrTiO3:Rh, SrTiO3:La / Rh, SrTiO3:Rh / Sb, SrTiO3:Ir, CaTiO3:Rh, La2Ti2O7:Cr, La2Ti2O7:Cr / Sb, La2Ti2O7:Fe, PbMoO4:Cr, RbPb2Nb3O 10 , HPb2Nb3O 10 , PbBi2Nb2O9, BiCu2VO6, BiSn2VO6, SnNb2O6, AgNbO3, AgVO3, AgLi 1 / 3 Ti 2 / 3 O2, AgLi 1 / 3 Sn 2 / 3 O2, etc., oxides such as LaTiO2N, Ca 0.25 La 0.75 TiO 2.25 N 0.75 , TaON, CaNbO2N, CaTaO2N, SrTaO2N, BaTaO2N, LaTaON2, Y2Ta2O5N2, (Ga 1-x Zinc x )(N 1-x O x ), (Zn 1+x Ge)(NO x ) (x represents a number between 0 and 1), TiN x O y F z, nitrides such as Ta3N5, GaN:Mg, sulfides such as CdS, selenides such as CdSe, Ln2Ti2S2O5 (Ln:Pr, Nd, Sm, Gd, Tb, Dy, Ho, and Er), Y2Ti2S2O5, and oxysulfide compounds including La and In (Chemistry Letters, 2007, 36, 854-855), but are not limited to the materials exemplified here.

[0016] In addition to visible light responsive optical semiconductors, ultraviolet light responsive optical semiconductors carrying a sensitizer can also be used. Specifically, ultraviolet light responsive optical semiconductors include TiO2, CaTiO3, SrTiO3, Sr3Ti2O7, Sr4Ti3O7, K2La2Ti3O 10 , Rb2La2Ti3O 10 , Cs2La2Ti3O 10 , CsLaTi2NbO 10 , La2TiO5, La2Ti3O9, La2Ti2O7, La2Ti2O7:Ba, KaLaZr 0.3 Ti 0.7 O4, La4CaTi5O7, KTiNbO5, Na2Ti6O 13 , BaTi4O9, Gd2Ti2O7, Y2Ti2O7, (Na2Ti3O7, K2Ti2O5, K2Ti4O9, Cs2Ti2O5, H + -Cs2Ti2O5(H + -Cs is Cs H + (The same applies below.) Cs2Ti5O 11 , Cs2Ti6O 13 , H + -CsTiNbO5, H + -CsTi2NbO7, SiO2-pillared K2Ti4O9, SiO2-pillared K2Ti 2.7 Mn 0.3 O7 (J. Mol. Catal. A: Chem. 2000, 155, 131)) (titanium oxide);

[0017] ZrO2, Na2W4O 13 ; K4Nb6O 17, Rb4Nb6O 17 , Ca2Nb2O7, Sr2Nb2O7, Ba5Nb4O 15 , NaCa2Nb3O 10 , ZnNb2O6, Cs2Nb4O 11 , La3NbO7(H + -KLaNb2O7, H + -RbLaNb2O7, H + -CsLaNb2O7, H + -KCa2Nb3O 10 , SiO2-pillared KCa2Nb3O 10 (Chem.Mater.1996, 8, 2534.), H + -RbCa2Nb3O 10 , H + -CsCa2Nb3O 10 , H + -KSr2Nb3O 10 , H + -KCA2NaNb4O 13 )(Above, niobium oxides);

[0018] Ta2O5, K2PrTa5O 15 , K3Ta3Si2O 13 , K3Ta3B2O 12 , LiTaO3, NaTaO3, KTaO3, AgTaO3, KTaO3:Zr, NaTaO3:La, NaTaO3:Sr, Na2Ta2O6, K2Ta2O6(pyrochlore), K2Ta2O6(pyrochlore), CaTa2O6, SrTa2O6, BaTa2O6, NiTa2O6, Rb4Ta6O 17 , H2La 2 / 3 Ta2O7, K2Sr 1.5 Ta3O 10 , LiCa2Ta3O 10 , KBa2Ta3O 10 , Sr5Ta4O 15 , Ba5Ta4O 15 , H 1.8 Sr 0.81 Bi 0.19 , Ta2O7, Mg-Ta oxide(Chem.Mater.2004 16, 4304-4310), LaTaO4, La3TaO7(Above, tantalum oxides);

[0019] PbWO4, RbWNbO6, RbWTaO6, CeO2:Sr, BaCeO3, (Bi2W2O9, Bi2Mo2O9, BaBi4Ti4O 15 , Bi3TiNbO9, PbMoO4, (NaBi) 0.5 MoO4, (AgBi) 0.5 MoO4, (NaBi)WO4, (AgBi) 0.5 WO4, Ga 1.14 In 0.86 O3, Ti 1.5 Zr 1.5 (PO4)4), NaInO2, CaIn2O4, SrIn2O4, LaInO3, YxIn2-xO3, NaSbO3, CaSb2O6, Ca2Sb2O7, Sr2Sb2O7, Sr2SnO4, ZnGa2O4, Zn2GeO4, LiInGeO4, Ga2O3, Ga2O3:Zn, etc. Also, as a sensitizer, [Ru(bpy)3] 2+ , erythrosine, zinc porphyrin, CdS, etc.

[0020] In addition, a p-type or n-type optical semiconductor may be adsorbed on the surface of the visible light responsive optical semiconductor to form a pn junction. Specifically, inorganic semiconductors such as CuO, Cu2O, CuI, Cu(InGa)S2, Cu(InGa)Se2, CuGaS2, CuGaSSe, CuGaSe2, CdS, CdTe, CdZnTe, CdSe, Cu2ZnSnS4, CuGa5S8, CuInS2, Cu(InAl)Se2, CuIn5S8, CuAlO2, CuGaO2, SrCu2O2, GaP, GaAs, GaAsP, GaN, InP, InAs, GaInAsP, GaSb, Si, SiC, Ge, ZnS, and Fe2O3 may be used. Semiconductors and organic semiconductors such as fullerene derivatives, porphyrin derivatives, phthalocyanine derivatives, and polythiophene derivatives can be used, but are not limited to the materials exemplified here.

[0021] Among these, the visible light responsive photosemiconductors are preferably used because they can directly use visible light and are advantageous in terms of production, and among these, the compound represented by the following general formula (1) is more preferred. Ba (1-a) TaO (2-b) N (1-c) (1) (In the formula, a, b, and c satisfy -0.2≦a≦0.1, -0.4≦b≦0.2, and -0.1≦c≦0.3, respectively.)

[0022] The shape of the photocatalyst is not particularly limited, but is preferably particulate, and the particle size of the primary particle is not particularly limited, but is usually 0.001 μm or more, preferably 0.005 μm or more, and usually 500 μm or less, preferably 20 μm or less, more preferably 10 μm or less. The particle size of the photocatalyst can be appropriately measured by known means such as XRD, TEM, and SEM.

[0023] (Co-catalyst) The cocatalyst supported on the photocatalyst may be a conventionally known one. Specifically, the cocatalyst may be a metal of Groups 3 to 13, an intermetallic compound of the metal, an alloy, or an oxide, composite oxide, oxynitride, sulfide, oxysulfide, carbide, nitride, or a mixture of these. Here, the term "intermetallic compound" refers to a compound formed from two or more metal elements, and the atomic ratio of components constituting the intermetallic compound is not necessarily stoichiometric, but has a wide composition range. "These oxides, composite oxides, oxynitrides, sulfides, oxysulfides, carbides, and nitrides" refers to metals of Groups 3 to 13, an intermetallic compound of the metal, an oxide of an alloy, a composite oxide, oxynitride, sulfide, oxysulfide, carbide, or nitride. "Mixtures of these" refers to a mixture of two or more of the compounds exemplified above.

[0024] The promoter preferably contains at least one selected from the group consisting of precious metals, and the precious metal may be an alloy or oxide containing the precious metal. Specific examples of the precious metal include Au, Ag, Pt, Pd, Rh, Ir, Ru, and Os, and among these, it is preferable to contain Pt.

[0025] The amount (total amount) of the cocatalyst supported on the photocatalyst is not particularly limited, but is usually 0.01 wt% or more, and may be 0.1 wt% or more, and is usually 5 wt% or less, and may be 3 wt% or less, and may be 1 wt% or less, based on the photocatalyst (100 wt%). The term "supported amount" used herein refers to the amount of the metal element in the supported promoter.

[0026] (First Step) The first step is to support a co-catalyst on the surface of the photocatalyst by impregnation. The impregnation method involves adsorbing promoter particles (colloids, etc.) or a compound that will be the precursor of the promoter onto the surface of the photocatalyst in a solution, evaporating the solvent of this solution if necessary, drying the sample, and then treating it in a reducing atmosphere such as hydrogen or ammonia (hydrogen reduction), or in a solution containing a reducing agent such as NaBH4 or alcohol (chemical reduction), or in an inert atmosphere such as nitrogen or argon (thermal decomposition treatment), or in an oxidizing atmosphere such as air, oxygen, or oxygen diluted with an inert gas (calcination), in order to support the promoter on the surface of the photocatalyst.

[0027] As a specific example, first, the cocatalyst particles (colloids, etc.) or a compound that is a precursor of the cocatalyst is dissolved in a solvent such as water, THF, or ethanol, and the photocatalyst particles are suspended in this solution. This suspension is stirred for 1 minute to 12 hours to allow the co-catalyst particles or the compound that will be the precursor of the co-catalyst to be adsorbed onto the surface of the photocatalyst. During the suspension, ultrasonic treatment may be performed, which disperses the photocatalyst particles well and promotes the adsorption of the promoter particles or the compound serving as the precursor of the promoter to the photocatalyst surface.

[0028] Then, the suspension is filtered or the solvent is dried up, and then the photocatalyst carrying the co-catalyst is obtained by treating the sample in a hydrogen gas atmosphere at 50 to 500°C for 0.5 to 12 hours (hydrogen reduction step described later). Note that, before hydrogen reduction of the dried-up sample, a calcination step may be inserted in which the sample is treated in an inert atmosphere such as nitrogen or argon, or in an oxidizing atmosphere such as air, oxygen, or oxygen diluted with an inert gas. The particle size of the promoter particles after loading is not particularly limited, but is usually 1 nm or more, preferably 2 nm or more, and usually 100 nm or less, preferably 50 nm or less. By making the particle size equal to or more than the lower limit mentioned above, the handling property is improved, and by making the particle size equal to or less than the upper limit mentioned above, a sufficient surface area can be secured, and the effect as a promoter is improved.

[0029] In the first step, the amount of the co-catalyst supported on the photocatalyst is not particularly limited, but since the co-catalyst is further supported in the second step, it is preferable not to support too much. Based on the photocatalyst as a standard (100 wt%), it is preferable that the amount is 1 wt% or less, and more preferably 0.5 wt% or less. There is no particular lower limit, but in order to obtain a sufficient probability of being supported on the highly active points, it is usually 0.001 wt% or more, and preferably 0.005 wt% or more.

[0030] (Second step) The second step is a step of supporting a co-catalyst similar to the co-catalyst used in the first step on the surface of the photocatalyst that has been supported by the first step, by photoelectrodeposition. The photoelectrodeposition method is a method in which a photocatalyst carrying a co-catalyst through the first step is suspended (dispersed) in a solution containing co-catalyst particles (colloids, etc.) or a compound that will be the precursor of the co-catalyst, the co-catalyst particles (colloids, etc.) or the compound that will be the precursor of the co-catalyst are adsorbed onto the surface of the photocatalyst, and the solution is irradiated with light for reduction, thereby carrying the co-catalyst on the surface of the photocatalyst. A specific example of the second step is shown below.

[0031] First, the co-catalyst particles or a compound serving as a precursor of the co-catalyst are dissolved in a solvent such as water, THF, or ethanol, and the co-catalyst-supported photocatalyst obtained in the first step is suspended in this solution. The solvent may be the same as that used in the first step. The suspension is irradiated with light capable of exciting the photocatalyst at room temperature for several hours in the absence of air and oxygen to support the co-catalyst. Usually, the suspension is used as is for the water splitting reaction, but after that, the suspension may be filtered or the solvent may be dried up, and then the suspension may be treated in an inert atmosphere such as nitrogen or argon, or may be calcined in an oxidizing atmosphere such as air, oxygen, or oxygen diluted with an inert gas, or may be reduced by hydrogen in a hydrogen atmosphere. In the second step, the amount of the co-catalyst supported on the photocatalyst is not particularly limited.

[0032] In the second step, a cocatalyst having the same composition as the cocatalyst supported in the first step is supported on the photocatalyst, but a different type of cocatalyst may also be supported. Here, the cocatalyst having the same composition includes a cocatalyst having the same composition as the cocatalyst supported in the first step, and a cocatalyst containing an oxide, composite oxide, oxynitride, sulfide, oxysulfide, carbide, or nitride of a metal or alloy containing the same metal as that contained in the cocatalyst.

[0033] (Hydrogen reduction step) The first step preferably includes a hydrogen reduction step in which the co-catalyst is reduced with hydrogen. The method of reducing the cocatalyst with hydrogen is not particularly limited, and for example, hydrogen gas may be contacted with the cocatalyst, optionally together with a carrier gas, which may be an inert gas such as nitrogen gas or argon gas. The contact temperature between the hydrogen gas and the promoter is usually 50°C or higher, preferably 150°C or higher, and more preferably 200°C or higher, and is usually 400°C or lower, and preferably 300°C or lower. Also, the contact time only needs to be sufficient for the promoter to be reduced, usually 0.25 hours or more, preferably 0.5 hours or more because sufficient reduction can be achieved, usually 3 hours or less, and preferably 1 hour or less.

[0034] (Promoter-supported photocatalyst) The photocatalyst supporting the promoter obtained through the above first step and second step has high hydrogen generation ability by water splitting. For example, when 0.1 g of the above promoter-supported photocatalyst is added to 150 mL of a 15 vol% methanol aqueous solution at 288 K and irradiated with light in the visible light region (λ≧420 nm) of a 300 W xenon lamp, the hydrogen generation rate can reach 250 μmol / h or more. In a preferred form, it can reach 300 μmol / h or more, 400 μmol / h or more, and in a particularly preferred form, 500 μmol / h or more.

Examples

[0035] Hereinafter, examples are shown to explain the present invention in more detail, but the scope of the present invention is not limited by the examples. <Preparation of BaTaO2N> As starting materials, powder reagents of BaCO3 and Ta2O5 were used, and powder reagents of chlorides (NaCl, KCl, CsCl, RbCl or BaCl2·2H2O) were used as fluxes. BaCO3 and Ta2O5 were weighed so that the molar ratio of Ba / Ta was 1.1. Also, each powder reagent was weighed so that the target BaTaO2N concentration was 10 mol% or 50 mol% (only 10 mol% and 50 mol% were carried out in the case of BaCl2 flux).

[0036] The weighed powder reagents were put into a mortar and dry-mixed. The dry-mixed powder was filled into an alumina container and placed in an alumina tube. The alumina tube was placed in a tubular furnace and heated in an ammonia gas stream at 200 mL / min. The temperature was raised to 950 °C at a rate of 600 °C / h and held at that temperature for 8 h.

[0037] After the holding, the alumina container was naturally cooled in an ammonia stream until it reached 300°C, and then in a nitrogen stream until it reached the removal temperature (80-100°C) after 300°C, and then the container was removed. In order to separate the remaining flux (chloride) from the BaTaO2N crystals, the flux was dissolved and removed by immersing the container in hot water at 80°C. Finally, the container was dried at 100°C, and crystals of BaTaO2N(RbCl), BaTaO2N(CsCl), BaTaO2N(KCl), BaTaO2N(NaCl), and BaTaO2N(BaCl2) were obtained according to the chloride. The formation of the target product was confirmed by XRD (Cu-Kα) (Figure 1). The obtained crystals also showed light absorption up to 670 nm in the UV-vis diffuse reflectance spectrum (Figure 2). The composition ratio of the obtained BaTaO2N by ONH meter and ICP analysis is as shown in Table 1.

[0038] [Table 1]

[0039] <PtO x / Preparation of WO3> WO3 (99.99%) manufactured by Kojundo Chemical Co., Ltd. was impregnated into an aqueous solution of H2PtCl6 so that the amount of Pt was 0.5 wt% relative to the amount of WO3. After evaporation to dryness, the sample was baked at 823 K for 30 minutes to obtain PtO x / WO3 was prepared.

[0040] <H-Cs-PtO x / Preparation of WO3> According to the method described in Catal. Sci. Technol., 2013, 3, 1750-1756, H-Cs-PtO x WO3 (99.99%) manufactured by Kojundo Chemical Co., Ltd. was impregnated into an aqueous solution of H2PtCl6 so that the amount of Pt was 0.5 wt% relative to the amount of WO3. After evaporation to dryness, the sample was baked at 823 K for 30 minutes to obtain PtO x / WO3 was prepared. xThe Cs / WO3 was impregnated into a Cs2CO3 aqueous solution so that the molar ratio of Cs / W was 0.01. After evaporation to dryness, the sample was baked at 773 K for 10 min to obtain Cs-PtO x / WO3 was prepared. Cs-PtO x / WO3 was stirred in 1M dilute sulfuric acid at room temperature for 1 hour, filtered, and dried at room temperature to obtain H-Cs-PtO x / WO3 was obtained.

[0041] <Photocatalytic activity evaluation> The photocatalytic reaction was carried out in a closed circulation evaluation device using a top-illuminated reaction cell with a Pyrex window. The hydrogen production rate in 150 mL of methanol aqueous solution (methanol concentration 15 vol%) was measured using a 300 W xenon lamp equipped with a cold mirror and a cutoff filter (L42, λ≧420 nm). The distance between the xenon lamp (light irradiation port) and the surface of the photocatalyst suspension was 7 cm. The temperature was controlled by a cooling water circulation device so that the reaction solution temperature was 288 K. The generated gas was analyzed by a gas chromatograph analyzer (TCD-GC, Shimadzu GC-8A, Molecular sieve 5A column) using Ar gas as the carrier gas.

[0042] Example 1: Preparation of 0.01wt%+0.09wt% Pt / BaTaO2N(RbCl) The obtained BaTaO2N(RbCl) was loaded with Pt as a promoter by the following procedure: Preparation of 0.01wt%Pt / BaTaO2N(RbCl) by impregnation method First, BaTaO2N (0.12 g) was suspended in a small amount of water containing dissolved HPtCl6·6H2O (>98.5%; Kanto Chemical Co., Ltd.) (the amount of HPtCl6·6H2O was adjusted so that the amount of Pt was 0.01 wt% of BaTaO2N). The suspension was mixed uniformly by ultrasonic treatment for 5 minutes. The suspension was then thoroughly dried and reduced with hydrogen at 473 K for 1 hour under a mixed gas flow of H2 and N2 (H2 concentration in the mixed gas flow was 10 vol%) to prepare 0.01 wt% Pt / BaTaO2N.

[0043] Preparation of 0.01wt%+0.09wt%Pt / BaTaO2N(RbCl) by photoelectrodeposition 0.1 g of the 0.01 wt% Pt / BaTaO2N powder prepared above was added to 150 mL of methanol aqueous solution containing dissolved H2PtCl6·6H2O (the amount of H2PtCl6·6H2O was adjusted so that the methanol concentration was 15 vol%, and the amount of Pt was 0.09 wt% of BaTaO2N). The suspension was placed in a closed circulation evaluation device, and cocatalyst loading and activity evaluation were carried out simultaneously as described in the above <Photocatalytic activity evaluation>. Here, photoelectrodeposition of Pt occurred quickly without an induction period, and 0.01wt%+0.09wt%Pt / BaTaO2N was produced. The hydrogen gas production rate of the photocatalyst was evaluated directly using the suspension that had been subjected to the photoelectrodeposition operation, without isolating the photocatalyst produced after the photoelectrodeposition operation.

[0044] Comparative Example 1: Preparation of 0.01 wt% Pt / BaTaO2N(RbCl) BaTaO2N (0.12 g) was suspended in a small amount of water containing dissolved HPtCl6·6H2O (>98.5%; Kanto Chemical Co., Ltd.) (the amount of HPtCl6·6H2O was adjusted so that the amount of Pt was 0.01 wt% of BaTaO2N). The suspension was mixed uniformly by ultrasonic treatment for 5 minutes. The suspension was then thoroughly dried and reduced with hydrogen at 473 K for 1 hour under a mixed gas flow of H2 and N2 (H2 concentration in the mixed gas flow was 10 vol%) to prepare 0.01 wt% Pt / BaTaO2N(RbCl).

[0045] Comparative Example 2: Preparation of 0.09 wt% Pt / BaTaO2N(RbCl) 0.1 g of BaTaO2N(RbCl) powder was dispersed in 150 mL of methanol aqueous solution containing dissolved H2PtCl6·6H2O (methanol concentration 15 vol%, amount of H2PtCl6·6H2O was adjusted so that Pt amount was 0.09 wt% of BaTaO2N). The suspension was attached to a closed circulation evaluation device, and the temperature was adjusted with a cooling water circulator so that the water temperature was 288 K. After sufficient degassing, visible light irradiation (λ≧420 nm) was performed while stirring to prepare 0.09 wt% Pt / BaTaO2N(RbCl). The hydrogen gas production rate of the photocatalyst was evaluated as it was in the suspension that had been subjected to the photoelectrodeposition operation, without isolating the photocatalyst produced after this photoelectrodeposition operation.

[0046] Example 2: Preparation of 0.01wt%+0.09wt% Pt / BaTaO2N(KCl) The preparation was carried out in the same manner as in Example 1, except that the type of flux in Example 1 was changed from RbCl to KCl.

[0047] Example 3: Preparation of 0.01wt%+0.09wt% Pt / BaTaO2N(CsCl) The preparation was carried out in the same manner as in Example 1, except that the type of flux in Example 1 was changed from RbCl to CsCl.

[0048] Example 4: Preparation of 0.01wt%+0.19wt%Pt / BaTaO2N(RbCl) The same procedure as in Example 1 was used for preparation by the photoelectrodeposition method, except that the amount of H2PtCl6·6H2O was adjusted so that the amount of Pt was 0.19 wt% of BaTaO2N.

[0049] Example 5: Preparation of 0.01wt%+0.29wt%Pt / BaTaO2N(RbCl) The same procedure as in Example 1 was used for preparation by the photoelectrodeposition method, except that the amount of H2PtCl6·6H2O was adjusted so that the amount of Pt was 0.29 wt% of BaTaO2N.

[0050] Example 6: Preparation of 0.05wt%+0.25wt%Pt / BaTaO2N(RbCl) In the preparation by the impregnation method in Example 1, the amount of H2PtCl6·6H2O was Pt and the amount of BaTa The amount of H2PtCl6·6H2O was adjusted so that the Pt content was 0.25 wt% of BaTaO2N, and in the preparation by photoelectrodeposition, the amount of H2PtCl6·6H2O was adjusted so that the Pt content was 0.25 wt% of BaTaO2N.

[0051] Example 7: Preparation of 0.1wt%+0.1wt%Pt / BaTaO2N(RbCl) The same procedure as in Example 1 was used for preparation, except that in the preparation by the impregnation method in Example 1, the amount of H2PtCl6·6H2O was adjusted so that the amount of Pt was 0.1 wt% of the BaTaO2N, and in the preparation by the photoelectrodeposition method, the amount of H2PtCl6·6H2O was adjusted so that the amount of Pt was 0.1 wt% of the BaTaO2N.

[0052] Example 8: Preparation of 0.1wt%+0.2wt%Pt / BaTaO2N(RbCl) The same procedures as in Example 1 were used for preparation, except that in the impregnation method in Example 1, the amount of H2PtCl6·6H2O was adjusted so that the Pt content was 0.1 wt% of the BaTaO2N, and in the photoelectrodeposition method, the amount of H2PtCl6·6H2O was adjusted so that the Pt content was 0.2 wt% of the BaTaO2N.

[0053] Example 9: Preparation of 0.1wt%+0.3wt%Pt / BaTaO2N(RbCl) The same procedures as in Example 1 were used for preparation, except that in the impregnation method in Example 1, the amount of H2PtCl6·6H2O was adjusted so that the Pt content was 0.1 wt% of the BaTaO2N, and in the photoelectrodeposition method, the amount of H2PtCl6·6H2O was adjusted so that the Pt content was 0.3 wt% of the BaTaO2N.

[0054] Example 10: Preparation of 0.01wt%+0.09wt% Pt / BaTaO2N(NaCl) The preparation was carried out in the same manner as in Example 1, except that the type of flux in Example 1 was changed from RbCl to NaCl.

[0055] Example 11: Preparation of 0.01wt%+0.09wt%Pt / BaTaO2N (without flux) The same procedure as in Example 1 was followed except that no flux was used and the flux removal step was omitted.

[0056] Comparative Example 3: Preparation of 0.1 wt% Pt / BaTaO2N(RbCl) The same procedure was used to prepare the BaTaO2N nanoparticles by the impregnation method in Comparative Example 1, except that the amount of H2PtCl6·6H2O was adjusted so that the amount of Pt was 0.1 wt% of the BaTaO2N nanoparticles.

[0057] Comparative Example 4: Preparation of 0.3 wt% Pt / BaTaO2N(RbCl) The same procedure was used to prepare the BaTaO2N nanoparticles by the impregnation method in Comparative Example 1, except that the amount of H2PtCl6·6H2O was adjusted so that the amount of Pt was 0.3 wt% of the BaTaO2N nanoparticles.

[0058] Comparative Example 5: Preparation of 0.2 wt% Pt / BaTaO2N(RbCl) The same procedure was followed in the preparation by the photoelectrodeposition method in Comparative Example 2, except that the amount of H2PtCl6·6H2O was adjusted so that the amount of Pt was 0.2 wt% of BaTaO2N.

[0059] Comparative Example 6: Preparation of 0.3 wt% Pt / BaTaO2N(RbCl) The same procedure was followed in the preparation by the photoelectrodeposition method in Comparative Example 2, except that the amount of H2PtCl6·6H2O was adjusted so that the amount of Pt was 0.3 wt% of BaTaO2N.

[0060] According to the ICP analysis, the amounts of Pt supported in Example 8 and Comparative Examples 3 to 6 were as shown in Table 2 below. From this result, it can be seen that the deposition amount was almost as targeted.

[0061] [Table 2]

[0062] Furthermore, SEM and TEM observations showed that the promoter Pt particles supported in the two-step process of impregnation and photoelectrodeposition were more uniformly dispersed than those supported by the conventional impregnation and photoelectrodeposition methods (see Figures 4 and 5). The experimental results for the above samples are shown in Table 3 below.

[0063] [Table 3]

[0064] (Considerations of Examples 1 to 11 and Comparative Examples 1 to 6) As is clear from the results shown in Table 3, Example 1, in which the promoter Pt was supported in two stages by the impregnation method and the photoelectrodeposition method, had higher activity than the conventional impregnation method alone (Comparative Example 1) or the photoelectrodeposition method alone (Comparative Example 2). The amount of Pt supported in Example 1 is different from that in Comparative Examples 1 and 2, but even if the hydrogen production rates in Comparative Examples 1 and 2 are added together, the activity of Example 1 is higher than that of Comparative Examples 1 and 2. The hydrogen production rate was lower than that of Example 1, and the activity was higher than that of the impregnation method (Comparative Example 3) with the same amount of Pt supported, demonstrating the effect of supporting the promoter Pt in two stages, the impregnation method and the photoelectrodeposition method.

[0065] Furthermore, as is clear from a comparison of Examples 4 and 7 with Comparative Example 5, and Examples 5 and 6 with Comparative Examples 4 and 6, Examples 4 to 7, in which the promoter Pt was supported in two stages, that is, the impregnation method and the photoelectrodeposition method, had higher activity than Comparative Examples 4 to 6, which had the same amount of Pt supported, demonstrating the effect of supporting the promoter Pt in two stages, that is, the impregnation method and the photoelectrodeposition method.

[0066] Similarly, as in Examples 2 and 3, even when the preparation method of BaTaO2N was changed, activity similar to that of Example 1 was obtained, demonstrating that the two-step support of the impregnation method and photoelectrodeposition method is effective regardless of the preparation method of BaTaO2N. Also, even when an inappropriate flux was used as in Examples 10 and 11, a higher hydrogen production rate was shown than when Comparative Examples 1 and 2 were simply added together, and from this point of view, it is clear that the product obtained by the method of this example has extremely high catalytic ability.

[0067] <Photocatalytic Activity Evaluation by Z-Scheme (Evaluation by Xenon Lamp)> 150 mL of 5 mM aqueous NaI solution was suspended with Pt / BaTaO2N (0.1 g) and 0.5 wt% PtO x / WO3 (0.1 g) was placed in an upper surface irradiation type reaction cell with a Pyrex window, and the hydrogen and oxygen generation rates were measured using a closed circulation evaluation apparatus. The gas generation rate was measured using a 300 W xenon lamp equipped with a cold mirror and a cut-off filter (L42, λ≧420 nm). The distance between the xenon lamp (light irradiation port) and the water surface of the photocatalyst suspension was set to 7 cm. The temperature was controlled by a cooling water circulation device so that the reaction solution temperature was 288 K. The generated gas was analyzed using an Ar gas as a carrier gas and a gas chromatograph analyzer (TCD-GC, Shimadzu GC-8A, Molecular sieve 5A column).

[0068] As Evaluation Examples 1 to 3, for the samples of Examples 1, 3, and 8, the hydrogen and oxygen generation rates were evaluated according to the above-described method for evaluating photocatalytic activity by the Z-scheme. The experimental results are shown in Table 4 below.

[0069]

Table 4

[0070] (Consideration of Evaluation Examples 1 to 3) As shown in Table 4, in the photocatalytic activity evaluation by the Z-scheme, the hydrogen generation rates of Evaluation Examples 1 to 3 were compared with the hydrogen generation rate of about 7 μmol / h described in Non-Patent Document 1 (see Figure 7 of Non-Patent Document 1) evaluated using Pt / BaTaO2N supporting Pt by the impregnation method, which is a conventional method, and were sufficiently high, indicating the effectiveness of the method of supporting the co-catalyst Pt in two steps of the impregnation method and the photoelectrodeposition method. compared with the hydrogen generation rate of about 7 μmol / h described in Non-Patent Document 1 (see Figure 7 of Non-Patent Document 1) evaluated using Pt / BaTaO2N supporting Pt by the impregnation method, which is a conventional method, and were sufficiently high, indicating the effectiveness of the method of supporting the co-catalyst Pt in two steps of the impregnation method and the photoelectrodeposition method.

[0071] <Photocatalytic Activity Evaluation by Z-Scheme (Evaluation by Simulated Solar Light)> As the catalyst, instead of 0.5 wt% PtO x / WO3 (0.1 g), 0.5 wt% H-Cs-PtO x / WO3 (0.1g) was used, and the lamp used was changed from a 300W xenon lamp equipped with a cold mirror and a cutoff filter (L42, λ≧420nm) to a pseudo-sunlight irradiation device, and the irradiation area was increased to 14cm 2 The evaluation was performed in the same manner as in the photocatalytic activity evaluation by the Z scheme described above, except that the above-mentioned conditions were met. The results are shown in Table 5 as Evaluation Example 4.

[0072] [Table 5]

[0073] (Considerations for Evaluation Example 4) As shown in Table 5, in the photocatalytic activity evaluation using the Z scheme, a high hydrogen production rate was obtained even when the light source was changed from a xenon lamp to simulated sunlight. This demonstrated the effectiveness of the method of supporting the promoter Pt in two steps, the impregnation method and the photoelectrodeposition method, regardless of the light source.

[0074] (Evaluation example 5) <Evaluation of apparent quantum yield> The apparent quantum yield (the ratio of the number of photons involved in the reaction to the number of photons incident on the photocatalyst) was evaluated from the amount of hydrogen generated by the photocatalytic reaction. The hydrogen generation rate was evaluated using a top-illuminated reaction cell with a Pyrex window in a closed circulation evaluation system. The hydrogen generation rate in 150 mL of methanol aqueous solution (methanol concentration 15 vol%) was measured using a 300 W xenon lamp equipped with a cold mirror and a bandpass filter (λ = 420 nm). The distance between the xenon lamp (light irradiation port) and the water surface of the photocatalyst suspension was 7 cm. The temperature was controlled by a cooling water circulation system so that the reaction solution temperature was 288 K. The generated gas was analyzed by a gas chromatograph analyzer (TCD-GC, Shimadzu GC-8A, Molecular sieve 5A column) using Ar gas as the carrier gas. The photocatalyst 0.1 wt% + 0.2 wt% Pt / BaTaO2N(RbCl) obtained in Example 8 had a hydrogen production rate of 51 μmol / h when irradiated with monochromatic light at 420 nm, and an apparent quantum efficiency of 5.9%.

Claims

1. A method for producing a photocatalyst having a co-catalyst supported on its surface, comprising the steps of: A first step of supporting a co-catalyst on the surface of the photocatalyst by impregnation; A second step of supporting a co-catalyst having the same substance constituting the co-catalyst as the co-catalyst used in the first step on the surface of the photocatalyst that has been subjected to the first step by a photoelectrodeposition method, The particle size of the promoter is 1 nm or more and 100 nm or less, the co-catalyst comprises any one of a metal of Group 3 to 13, an intermetallic compound of the metal, an alloy, an oxide, a composite oxide, an oxynitride, a sulfide, an oxysulfide, a carbide, a nitride, or a mixture thereof; A method for producing a photocatalyst, wherein the photocatalyst is capable of generating hydrogen.

2. The method for producing a photocatalyst according to claim 1 , wherein the amount of the co-catalyst supported on the photocatalyst in the first step is 1 wt % or less.

3. The method for producing a photocatalyst according to claim 1 or 2, wherein the co-catalyst comprises one or more members selected from the group consisting of precious metals.

4. The method for producing a photocatalyst according to any one of claims 1 to 3, wherein the co-catalyst contains Pt.

5. The method for producing a photocatalyst according to any one of claims 1 to 4, wherein the photocatalyst comprises a compound represented by the following formula (1): Ba (1-a) Oh (2-b) N (1-c) ・・・(1) (In the formula, a, b, and c satisfy −0.2≦a≦0.1, −0.4≦b≦0.2, and −0.1≦c≦0.3, respectively.)

6. The method for producing a photocatalyst according to any one of claims 1 to 5, wherein the first step includes a hydrogen reduction step of reducing the co-catalyst with hydrogen.

Citation Information

Patent Citations

  • Photocatalyst comprising metal oxynitride having responsiveness to visible light

    JP2002066333A

  • Photocatalyst for water photolysis reaction and method for producing the same

    JP2011173102A

  • Production method of core-shell type photocatalyst, core-shell type photocatalyst, and water splitting method using core-shell type photocatalyst

    JP2015071128A